KNEE JOINT PROPRIOCEPTION AND QUADRICEPS MUSCLE STRENGTH AMONG DIABETIC AND NON DIABETIC SUBJECTS (International Journal of Physiotherapy, 2016)
Background: Diabetes mellitus is a group of metabolic disorders characterized by increased blood sugar (glucose) levels (hyperglycemia) with absolute/relative deficiency in carbohydrate, protein and fat metabolism caused by defect in insulin secretion, action of insulin or both. Diabetes mellitus can be combined with problems/impairments which can lead to the decrease in muscles strength and proprioception specially, in the lower limbs. The purpose of the study is to investigate the knee joint repositioning accuracy as a measure of knee joint proprioception and peak torque of the quadriceps muscle as a measure of quadriceps strength between type II diabetic patients (in the first five years of the disease) and healthy subjects.Methods: Thirty male subjects aged between 35–55 years old were included in this study; they were assigned into two equal groups, the study group which included15 type II diabetic patients in early five years of the disease and the control group which included 15 healthy subjects. Active knee joint repositioning accuracy as a measure of knee joint proprioception and the isokinetic peak torque of the quadriceps muscle as a measure of quadriceps strength were measured for both groups by Biodex multipoint system, pro Isokinetic dynamometer.Results: The unpaired t test results between the two groups showed no significant differences in knee joint repositioning errors where P-value was (0.319) and also there was no significant difference in quadriceps muscle strength between the control and study groups where the P-value was (0.157).Conclusion: Knee joint repositioning accuracy and quadriceps muscle strength aren't affected in type II diabetes mellitus patients in early five years of the disease.